2008
DOI: 10.1007/s00330-007-0835-3
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of intracranial internal carotid artery on 3D TOF MR angiography: a sign of unilateral extracranial stenosis

Abstract: The purpose of this case-control study was to determine whether an asymmetry of size of the intracranial internal carotid artery (ICA) on 3D time-of-flight MR angiography (MRA) is predictive of a high-grade cervical ICA stenosis. Ninety-six stroke/TIA consecutive patients were recruited for the study, of whom 32 had unilateral high-grade ICA stenosis (>or=70% NASCET) and were included into the case group, and the remaining 64 did not have such high-grade stenosis and were included in the control group. On intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The size asymmetry of the intracranial ICAs reveals the presence of an underly-ing high-grade cervical stenosis, with a high degree of confidence, especially in patients without an anatomical variant of the anterior part of the Circle of Willis. Naggar et al (30) verified asymmetrical ICA in MR angiographic studies in 28 of 32 patients with a high degree of stenosis in the cervical segment of the ICA (≥70%). The reason for the size asymmetry of the intracranial ICAs may also be that the anterior part of the Circle of Willis is incomplete.…”
Section: Discussionmentioning
confidence: 90%
“…The size asymmetry of the intracranial ICAs reveals the presence of an underly-ing high-grade cervical stenosis, with a high degree of confidence, especially in patients without an anatomical variant of the anterior part of the Circle of Willis. Naggar et al (30) verified asymmetrical ICA in MR angiographic studies in 28 of 32 patients with a high degree of stenosis in the cervical segment of the ICA (≥70%). The reason for the size asymmetry of the intracranial ICAs may also be that the anterior part of the Circle of Willis is incomplete.…”
Section: Discussionmentioning
confidence: 90%
“…Alternatively, since flow in both ICAs is assumed to be equal in healthy persons, which is supported by our own data, we chose to use the unaffected side as comparison [25]. Another study already has shown that extracranial ICAS leads to significant reduction of the surface region distally by measuring the surface area and evaluating vessel asymmetry [26]. We consider C3/C4-SIR a more objective and investigator-independent method.…”
Section: Discussionmentioning
confidence: 98%
“…Although CTA examination is an effective method to evaluate ICAS, in clinical practice ( Osephson et al, 2004 ), cervical CTA or ultrasound examination is often not performed promptly in patients with ischemia, which may omit the consideration of the condition of neck vessels. Previous studies have shown that asymmetry of the intracranial segment of the ICA suggests severe stenosis in an ICA ( Naggara et al, 2008 ). In cases of severe ICAS, a high proportion of unilateral A1 dysplasia or underdevelopment was observed on CTA that was attributed to the anatomic variation of the circle of Willis in previous studies ( Waaijer et al, 2007 ; Varga et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%